Electrophysiology of Inhibitory Control in the Context of Emotion Processing in Children With Autism Spectrum Disorder - Magnuson, Justine R.; Peatfield, Nicholas A.; Fickling, Shaun D.; Nunes, Adonay S.; Christie, Greg; Vakorin, Vasily; D’Arcy, Ryan C. N.; Ribary, Urs; Iarocci, Grace; Moreno, Sylvain; Doesburg, Sam M. (Frontiers in Human Neuroscience, 2019)
Autism Spectrum Disorder (ASD) is an increasingly common developmental disorder that affects 1 in 59 children. Despite this high prevalence of ASD, knowledge regarding the biological basis of its associated cognitive difficulties remains scant. In this study, we aimed to identify altered neurophysiological responses underlying inhibitory control and emotion processing difficulties in ASD, together with their associations with age and various domains of cognitive and social function. This was accomplished by assessing electroencephalographic recordings during an emotional go/nogo task alongside parent rating scales of behaviour. Event related potential (ERP) N200 component amplitudes were reduced in children with ASD compared to typically developing (TD) children. Consistent with previous findings, increased age correlated with improved behavioral accuracy and reduced N200 amplitude in the TD group, indicating that as these children develop, their neural systems become more efficient. These associations were not identified in the ASD group. Results also showed significant associations between increased N200 amplitudes and improved executive control abilities and decreased autism traits in TD children only. The newly discovered findings of decreased brain activation in children with ASD, alongside a lack of correlation with age and behavioural scores, provide a potential neurophysiological indicator of atypical development of inhibitory control mechanisms in these individuals.